2012
DOI: 10.1101/cshperspect.a012286
|View full text |Cite
|
Sign up to set email alerts
|

P-Bodies and Stress Granules: Possible Roles in the Control of Translation and mRNA Degradation

Abstract: The control of translation and mRNA degradation is important in the regulation of eukaryotic gene expression. In general, translation and steps in the major pathway of mRNA decay are in competition with each other. mRNAs that are not engaged in translation can aggregate into cytoplasmic mRNP granules referred to as processing bodies (P-bodies) and stress granules, which are related to mRNP particles that control translation in early development and neurons. Analyses of P-bodies and stress granules suggest a dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
685
1
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 698 publications
(711 citation statements)
references
References 134 publications
20
685
1
5
Order By: Relevance
“…However, several studies have found that mRNA decay enzymes such as XRN1 can be also found in SGs, suggesting that mRNA degradation may also take place in these foci. 8,14 Likewise, we showed that TSN is localized in both SGs and PBs and that enzymatically active tandem repeat of 4 N-terminally situated SN domains confers this localization. 11 TSN is an evolutionarily conserved protein present in almost all eukaryotes, with the notable exception of Saccharomyces cerevisiae.…”
mentioning
confidence: 86%
“…However, several studies have found that mRNA decay enzymes such as XRN1 can be also found in SGs, suggesting that mRNA degradation may also take place in these foci. 8,14 Likewise, we showed that TSN is localized in both SGs and PBs and that enzymatically active tandem repeat of 4 N-terminally situated SN domains confers this localization. 11 TSN is an evolutionarily conserved protein present in almost all eukaryotes, with the notable exception of Saccharomyces cerevisiae.…”
mentioning
confidence: 86%
“…This pathway is thus complementary to cytoplasmic RNA degradation pathways, in which different classes of ribonucleases and degradation machineries function. 64,65 Studies in multiple systems have found RNS2 orthologs to be important for the degradation of rRNA. Mutant alleles of RNASET2 are associated with accumulation of undigested rRNA within lysosomes in zebrafish and human neurons, 18,66 and rRNA is a cellular substrate for the RNase T2 enzymes of unicellular eukaryotes such as yeast and Tetrahymena during nutrient starvation.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylation of eIF2α, 4E-BPS, and other initiation factors negatively impacts translation (Pavitt and Ron, 2012). In addition to the regulation of translation initiation, mRNA can be sequestered into stress granules or P-bodies upon translation inactivation in response to stresses (Decker and Parker, 2012). Nonsense mediated decay ensures translation fidelity by screening mRNAs for premature stop codons and mediating their decay (Hentze and Kulozik, 1999;Maquat, 2004).…”
Section: Translation Regulation Through Reversible Trna Methylationmentioning
confidence: 99%